Recent advances on convolutional architectures in medical applications: classical or quantum - DURU, ADİL DENİZ (My University, 2022)
© 2022 IEEE.Deep learning is one of the most significant advances in AI (AI). It is used in a variety of fields due to it has the ability to solve problems that cannot be handled by traditional technologies. The optimization of deep learning relevant to medical images is one of the most important recent advances in image analysis. Several developments have been done on Convolutional Neural Networks to achieve optimal accuracy and increase the learning speed. However, in this paper, we discuss the most recent innovations in convolutional neural networks within Classical method and Quantum method. We briefly provide a snapshot about the architecture, improvements, and principles of both (Classical and Quantum).
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Bilgisayar Bilimleri; Algoritmalar; İnşaat Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Library Sciences; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Control and System Engineering; Computer Sciences; algorithms; Civil Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Mühendislik; Sosyal Bilimler Genel; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; TELEKOMÜNİKASYON; ENERJİ VE YAKITLAR; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; MÜHENDİSLİK, İNŞAAT; Engineering, Computing & Technology (ENG); Social Sciences (SOC); COMPUTER SCIENCE; ENGINEERING; SOCIAL SCIENCES, GENERAL; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; TELECOMMUNICATIONS; ENERGY & FUELS; INFORMATION SCIENCE & LIBRARY SCIENCE; ENGINEERING, CIVIL; Yapay Zeka; Fizik Bilimleri; Bilgisayar Ağları ve İletişim; Bilgisayar Bilimi Uygulamaları; Bilgi Sistemleri ve Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; İnşaat ve Yapı Mühendisliği; Kontrol ve Optimizasyon; Artificial Intelligence; Physical Sciences; Computer Networks and Communications; Computer Science Applications; Information Systems and Management; Social Sciences & Humanities; Renewable Energy, Sustainability and the Environment; Civil and Structural Engineering; Control and Optimization; Classification; Convolutional Neural Networks; Deep learning; Medical images; Quantum Convolutional Neural Networks; —Quantum Convolutional Neural Networks; Convolutional Neural Networks; Classification; Medical images; Deep learning